Gra RPG (role-playing game) jako praktyka kulturalna. Refleksje socjologiczne = The RPG game as a cultural practice: sociological reflections - Trzop, Beata (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article attempts to analyze participation in role-playing games (RPGs) as a distinctive cultural practice, drawing on Zygmunt Bauman`s concept of retrotopia, Simon Reynolds` notion of retromania, and Johan Huizinga`s classical theory of play. The empirical foundation of the study is based on data collected during an experiment conducted at the Krzywaniec correctional facility by Michał Bańka, a professional RPG master.
Keywords: retromania; retrotopia; zabawa; gry RPG; praktyka kulturalna; play; cultural practices